2005
DOI: 10.1016/j.cell.2005.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Regulatory Particle Alters the SAGA Coactivator to Enhance Its Interactions with Transcriptional Activators

Abstract: Promoter recruitment of the Saccharomyces cerevisiae SAGA histone acetyltransferase complex is required for RNA polymerase II-dependent transcription of several genes. SAGA is targeted to promoters through interactions with sequence-specific DNA binding transcriptional activators and facilitates preinitiation-complex assembly and transcription. Here, we show that the 19S proteasome regulatory particle (19S RP) alters SAGA to stimulate its interaction with transcriptional activators. The ATPase components of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
158
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(177 citation statements)
references
References 54 publications
(75 reference statements)
15
158
0
Order By: Relevance
“…We also demonstrate here that 19 S ATPase activity stimulates Gal4p-SAGA interaction. Consistent with our in vivo data, previous biochemical studies (13) have demonstrated the physical and genetic interactions between SAGA and the 19 S base. Interestingly, we find that Gal4p-SAGA interaction is essential for recruitment of the 19 S base at the GAL1 UAS.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We also demonstrate here that 19 S ATPase activity stimulates Gal4p-SAGA interaction. Consistent with our in vivo data, previous biochemical studies (13) have demonstrated the physical and genetic interactions between SAGA and the 19 S base. Interestingly, we find that Gal4p-SAGA interaction is essential for recruitment of the 19 S base at the GAL1 UAS.…”
Section: Discussionsupporting
confidence: 93%
“…However, the mechanisms by which the proteasome regulates eukaryotic transcriptional activation in a proteolysis-independent manner remain largely unknown. Recent biochemical studies (13,23) have demonstrated the nonproteolytic role of the proteasome in regulation of the activator-coactivator or activator-promoter interaction (and hence transcriptional activation). However, how the 19 S RP regulates transcriptional activation at the promoter is not yet clearly understood in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others later demonstrated that Rpt6, presumably acting in concert with the other proteins in the 19 S base, is also important in mediating histone modifications and in recruiting the SAGA complex to promoters. Neither of these activities require proteolysis (11,12).…”
mentioning
confidence: 99%